Advances and perspectives in modeling applied to forest planning in Mexico - Santiago-García, Wenceslao; Ángeles-Pérez, Gregorio; Quiñonez-Barraza, Gerónimo; De los Santos-Posadas, Héctor Manuel; Rodríguez-Ortiz, Gerardo (Instituto de Ecología, A.C., 2020)
In forestry there is a long history in the parameterization and use of models to quantify and predict the growth and yield of forest stands, as a fundamental requirement to optimize the application of silvicultural practices for sustainable forest management. The status of Mexico on the use and parameterization of forest models shows significant advances in recent years, which has resulted in the constant generation of biometric tools for the implementation of planning systems and forest management plans. Nevertheless, there is still an urgent need to generate biometric tools to optimize the processes of planning and utilization of forest resources. Currently, in Mexico there is an important collection of models for various purposes, such as volume models, taper models, compatible taper-volume systems, height-diameter models, site index models, biomass, carbon and nutrient content of ecosystems, density management; whole-stand, diameter distributions and individual tree growth models. Given the dynamic environment that involves using biologically more realistic variables to model physiological processes related to forest growth, much remains to be done in forest modeling in Mexico. However, important steps have been taken in the establishment of permanent sampling plots for the periodic measurement of forest growth, and the characterization of structural changes of forest stands. These, coupled with capacity building in biometrics and modeling throughout the country, make it possible to prognosticate important advances in this area in the near future.